SOCIAL WELL-BEING IN GEN Z INDIVIDUALS: EXAMINING THE CORRELATION WITH SELF-ESTEEM AND SOCIAL SUPPORT - Ndubuisi Odua, Victor (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2023)
Generation Z represents individuals born in the era of growing digital innovations, and they comprise most of the world's population. This study explored the correlation between this cohort's self-esteem, social support, and social well-being. Two hundred and twenty undergraduates enrolled in four public tertiary institutions in River State, Nigeria, were recruited. The male and female students were conveniently pooled from different departments in the selected institutions. The respondents completed a self-report measure of the Rosenberg Self-Esteem Scale (RSES), the Multidimensional Scale of Perceived Social Support (MSPSS), and The Social Well-being Scale. A Pearson moment model was computed to test the correlations among the study variables. The results indicated that self-esteem (r = .44, p< .01) and social support (r = .69, p< .001) positively correlated with social well-being in Gen Z. The study concludes that self-esteem and social support are essential determinants of social well-being in the Gen Z. The result has implications for enhancing the social well-being in younger individuals.